(3QSGdI aj GdYed HGdQHY GdeLjHs - (3YHO Gddg Hf Ndjd Hf jhSa, LeGd GdOjf GdeGQOGfj,J (B809 (3g` s ((3CMeO Hf ZHQGgje Hf fUQ Gddg GdcfGfi GdYSbdGfi GdMfHdi s)
(3ChdgG (B:s
(3HYO GdHSedI hGdMeO (B: (3agPg QSGdI ai GdYed HGdQHY GdeLjH ef cdGe GdTjN LeGd GdOjf YHO Gddg Hf Ndjd Hf jhSa GdTgjQ HGdeQGOjfi eTJedI Ydi ebOeI hYTQjf HGHG s
(3BNQgG (B:s
(3hgPG GdbOQ ajg caGjI ddeHJOF , hCSCd Gddg Cf jfaY HgG bGQFgG s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B53s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B169 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B48 s
Keywords: (3Gdadcs